PENGARUH PENDEKATAN BEHAVIORAL MODEL OPERANT CONDITIONING TERHADAP KARAKTER DISIPLIN SISWA SEKOLAH DASAR - Yusrizal; Fatmawati; Latifah Annisa; Danu Alpin Gustio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomenon of moral degradation among students is increasingly worrying. Therefore, it is necessary to make a change in learning that is oriented towards improving character. Related to this, this study generally aims to find a new paradigm through research results to improve student character. Specifically, this study aims to analyze the use of the behavioral model operant conditioning approach to the character of student discipline in elementary schools. This study is an experimental study by comparing the behavioral model operant conditioning approach with the value clarification technique approach. This study was conducted at SD Swasta PAB 27 Tj. Mulia. The sample used was 46 students. Data collection in this study used an observation sheet, while the research hypothesis was tested using an independent sample t test. The results of the study showed that there was a significant difference between the character of student discipline taught with the behavioral model operant conditioning approach compared to the value clarification technique approach. Students taught with the behavioral model operant conditioning approach had a higher character of discipline compared to students taught with the value clarification technique approach with a Mean Difference of 8.78.